Understanding Knowledge, Attitude, and Perception of Indian Clinicians in the Management of Resource-challenged Type 2 Diabetes Mellitus Patients in India - DESERVE India Expert Opinion: Part 1 - Unnikrishnan, Ambika G.; Patel, Abji B.; Kannan, Alagarsamy; Bagchi, Ananda; Laway, Bashir A.; Selvaraj, Chandrasekar; Sanyal, Debmalya; Dutta, Deep; Bandyopadhyay, Dipanjan; Chilakala, Gopinath R.; Shinde, Jaydeep S.; Vadgama, Jimit; et al. (Chronicle of Diabetes Research and Practice, 2025)
Introduction: Type 2 diabetes mellitus (T2DM), once perceived as a condition prevalent among affluent elderly urban residents, now affects a more diverse demographic, including populations from less-privileged and rural communities. While providing optimal care, clinicians face challenges, such as the financial constraints of T2DM patients. This underscores the urgent need for affordable interventions to enhance patient outcomes and the necessity for a comprehensive understanding of clinician knowledge, attitudes, and perceptions (KAPs). The aim of this study was to develop a consensus of Indian clinicians to emphasize the need for awareness and access to high-quality, affordable interventional approaches for effectively managing resource-challenged T2DM patients in India. Methods: A mixed method study, including 590 clinicians and 60 subject matter experts, assessed their KAPs regarding managing >18 years of adult resource-challenged (deserving) T2DM patients. A structured questionnaire gathered data on clinicians' clinical and management practices. Four days in-depth interview with 60 subject matter experts also facilitated the expert opinion development process, ensuring a comprehensive and reliable study. Data were analyzed using SPSS Version 29, with statistical significance at P < 0.05. Results: The findings of this study, based on the responses of 590 clinicians, are significant. About 38.64% of the clinicians encountered 1-5 resource-challenged T2DM patients daily, while 40.33% encountered 6-15 patients, reflecting a significant patient load. Concerning follow-up duration, 59.10% reported 1-3 months, highlighting the challenges in maintaining regular follow-ups. Over 80% agreed that these patients struggle to afford treatment and often miss follow-up appointments, seeking alternative therapies due to financial constraints, which can lead to suboptimal glycemic control (P < 0.001). In addition, 82.00% agreed that high cost and lack of financial resources as the primary reason for medication non-adherence. The majority of clinicians agreed that "Glipizide + Metformin could be optimally used for these patients" (P < 0.001). The expert panel identified financial constraints, lifestyle modification difficulties, and psychological challenges as key issues in managing resource-challenged T2DM patients in India. Conclusion: Clinicians and the expert panel agreed on several critical issues, including financial constraints and challenges in adopting lifestyle modifications to manage resource-challenged (deserving) T2DM patients. There is agreement on prescribing low-cost glucose-lowering medications with metformin and glipizide combinations to improve patient adherence and outcomes in resource-constrained settings.